Comparison of Effect on the Strength Training by Using Positive and Inverted Pyramid Methods - Yanna ZHU; Yupeng LIU; Guanghu YU; Junfeng GUO; Jun LONG; Shujie SU; Shunji SHEN (康复学报)
Objective:To compare the training effects of the quadriceps muscle strength of health adults under two training patterns: positive and inverted pyramid methods.Methods:Eighty health adults were divided into two groups: 40 subjects had strength training experience and the other 40 subjects did not have strength training experience. Twenty health adults were trained by the positive pyramid method, and the other 20 health adults were trained by the inverted pyramid method in each group.Results:Both of the two training patterns improved the quadriceps muscle strength of the subjects, and the positive pyramid method were more obvious for the subjects who did not have strength training experience (P<0.05), and the inverted pyramid method were more obvious for the subjects who had strength training experience (P<0.05).Conclusion:Both of the positive pyramid method and the inverted pyramid method can improve the quadriceps muscle strength of health adults. The positive pyramid method is more suitable for the health adults who do not have strength training experience and the inverted pyramid method is more suitable for the health adults who have strength training experience.